Society without the social: the Spanish labour movement and the rise of the social, 1840–1880. (1st October 2016) - de Felipe-Redondo, Jesus
Abstract: Focusing on the Spanish case, this article addresses two fundamental questions: why were many unionized workers sceptical about state intervention in labour issues throughout the nineteenth century, and why did this attitude begin to change from the 1860s onwards? Its main thesis is that workers' attitudes derived ultimately from different historical notions of 'society' that shaped their perceptions and experiences of labour relations and their attitude toward the role of the state. Thus, a notion of society as an aggregation of individuals shaped unionized Spanish workers' hostility toward state intervention since the creation of the first unions in the 1840s. From the 1860s onward, a new conception of collective relations, namely 'the social', began to transform some workers' expectations of the role of the state in labour conflicts. The main factor that explains this change, it is argued, lies in the relationship between the workers' imaginary, their actions, and their expectations about these actions.